Classical bifurcation at the transition from Rabi to Josephson dynamics - Zibold, Tilman; Nicklas, Eike; Gross, Christian; Oberthaler, Markus K. (Physical review letters, 2010)
We report on the experimental demonstration of the internal bosonic Josephson effect in a rubidium spinor Bose-Einstein condensate. The measurement of the full time dynamics in phase space allows the characterization of the theoretically predicted π-phase modes and quantitatively confirms analytical predictions, revealing a classical bifurcation. Our results suggest that this system is a model system which can be tuned from classical to the quantum regime and thus is an important step towards the experimental investigation of entanglement generation close to critical points.
Published 12 November 2010
Gesehen am 09.02.2024